The God must be crazy - Uy, Jamie (Quezon City : Magnavision.)
For five thousand years, things have stayed pretty much the same for Xi and his fellow Bushmen. Then one day, an empty coke bottle drops magically from the sky, and life goes topsyturvy in the face of this generous "gift of the Gods." When Xi sets off to return the mystical present, he encounters a romantic microbiologist, a school teacher and a band of terrorists all enmeshed in a plot so insane, it could only happen in the "civilized" world. An international sensation, THE GOD MUST BE CRAZY is one of the most original and thought-provoking comedies ever. starring a real-life Bushman N!xau, its a movie that lookat us from the other side-and shows us just how crazy we are!